Study of Emotional Intelligence of Sports Students - Nur Wisma; Ibnu Andli Marta (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the emotional intelligence possessed by students of the Department of Sports Education, Padang State University after Covid-19 hit Indonesia. Emotional intelligence or emotional quotient refers to abilitiesrecognizeown feelings and the feelings of others. This type of research was a quantitative descriptive involving 183 male students (124) and female students (59) who were still actively enrolled until the research was carried out using the accidental sampling technique. Data was collected using a Likert-scale questionnaire distributed with the Google form. The results of the study provide information that the level of emotional intelligence possessed by students is on average in the "Good" classification with a Respondent Achievement Level (TCR) value of 77.24%.